EFFORTS TO IMPROVE CHILDREN'S MOTIVATION AND RUDE MOTORS THROUGH GAME BANGLING AT SARASWATI PAUD, SURAKARTA CITY - Purwaningsih, Sri; Koesdyantho, A.R; Irmade, Oka (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This study aims to improve students' motivation and rough Motoricskills through propeller games at PAUD Saraswati, Surakarta in the 2019/2020 academic year. This research is a classroom action research (PTK) which uses a modified model of Kemmis and MC Taggart, the subjects of this study were 15 students. The data collection methods used were observation and documentation. The data analysis technique used quantitative descriptive. The indicator set is at least 75%. The results showed that the propeller game can improve motivation and rough Motoricskills of students in PAUD Saraswati, Surakarta. This is evidenced in the achievement of very well developed indicators. In cycle I, the students' motivation and gross motoric skills increased as much as 9 out of 15 students or 60% were in the criteria of starting to develop. Meanwhile, in cycle II, the students' motivation and rough Motoricskills increased by 13 students or 86.6% in the criteria of developing very well and developing according to expectations. This research was stopped until cycle II because it met the criteria for success indicators, namely at least 75% of the 15 students. The methods used are: 1) direct learning approach treatment with propeller game, 2) habituation carried out by the teacher. These actions can increase motivation and rough Motoricskills in students. Keywords: Motivation, Rough Motoric, The propeller game